Formy prawne współpracy transgranicznej w polskim porządku prawnym - Cendrowicz, Dominika (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
Because of the fact that the cross-border cooperation of the local government plays an important role in contemporary Europe, describing the subject associated with possibilities of its carrying out by the Polish local government is very important. Poland being a member of the European Union and a democratic law-governed state accepted the sequence of obligations authorizing Polish communes, districts and provinces to build up the outside cooperation with entities from othercountries. However the Polish law doesn’t determine structures of the cross-border cooperation. Therefore Polish communes, districts and provinces use: associations, civil-law partnerships and European groupings of territorial cooperation for its leading. The most popular form of the crossborder cooperation are assosiations which are agreements sides of Euroregions functioning on Poland borders. How the cross-border cooperation will look like and what benefits it will bring to entities leading it, it depends on legal possibilities for its leading. Hence describing the subject connected with legal forms of the cross-border cooperation avaiable for Polish local goverment is so important.
Keywords: współpraca transgraniczna; polskie prawo; euroregiony; stowarzyszenia